Safety climate perceived by pre-hospital emergency care personnel—an international cross-sectional study - Kosydar-Bochenek, Justyna; Religa, Dorota; Knap, Małgorzata; Czop, Marcin; Knap, Bartosz; Mędrzycka-Dąbrowska, Wioletta; Krupa, Sabina (Frontiers in Public Health, 2023)
Introduction Improving patient safety is one of the most critical components of modern healthcare. Emergency medical services (EMS) are, by nature, a challenging environment for ensuring patient safety. It is fast-paced, physically dangerous, and highly stressful, requiring rapid decision-making and action. This can create risks not only for patients but also for employees. We assessed variations in perceptions of safety culture in prehospital emergency care among an international sample of paramedics and nurses. Methods The Emergency Medical Services Safety Attitudes Questionnaire (EMS-SAQ) was used for the study. The instrument measures six domains of safety culture in the workplace: teamwork climate, job satisfaction, safety climate, working conditions, stress recognition, and perceptions of management. A total of 1,128 EMS from 9 countries participated in this study. Results Safety Climate was 81.32/100 (SD 6.90), Teamwork Climate 84.14/100 (SD 8.74), Perceptions of Management 76.30/100 (SD 10.54), Stress Recognition 89.86/100 (SD 5.70), Working Conditions 81.07/100 (SD 9.75), and Job Satisfaction 70.71/100 (SD 7.21). There was significant variation in safety culture scores across countries for teamwork climate (TWC), working conditions (WC), and job satisfaction (JS). Among the individual variables (age, gender, level of education, and work experience), variations in safety culture scores were unaffected by age, gender, or work experience. Organizational characteristics: employment status and position type were linked to significant variations in safety culture domain scores. Conclusion Participants’ perceptions of the patient safety climate were not particularly satisfactory, confirming that there is still a need to develop a culture of patient safety in prehospital emergency care.